The Influence Of Perceived Job Risk And Religiousness Towards Positivity And Helping Behaviour Among Government Girls’ Primary School Teachers In Northern Pakistan - Nisa, Zaib Un (2024)
The hegemony of terrorism in government girls' primary schools in Pakistan has postulated numerous challenges for the female teaching fraternity. Over the last decade, more than 90 terrorist attacks on government girls' primary schools in Pakistan have made female teachers’ life miserable. The lack of perceived organizational support and feeble safety and security measures amidst terrorism aggravated female teachers’ perceived job risk. The current study investigated the sensitive social issue of our society that warranted special attention. The results of the present study confirmed the devastating implications of female teachers' perceived threats of terrorism and lack of perceived organizational support, which caused high perceived job risk. Female teachers’ perceived job risk is constantly disturbing their positivity and helping behavior in the terrorism-affected schools of Pakistan. The present study administered a correlational research design and gathered data from the 303 female teaching fraternity of Pakistan’s terrorism-affected government girls' primary schools through a self-administered survey. The results attested to the significant and positive association of female teachers' perceived threats of terrorism with their perceived job risk. Further, the findings attested to the significant and negative association of female teachers' perceived organizational support with their perceived job risk. The results revealed that there is a significant and negative association between female teachers' perceived job risk and their positivity.